A Review of Neurobehavioral Challenges in Children Exposed Prenatally to Intrauterine Opioid - Kamaledin Alaedini; Kaveh Haddadi; Leila Asadian (Journal of Pediatrics Review, 2017)
Context: Substance abuse has remained a worldwide issue for many years and in recent decades there has been a major growth in the number of individuals consuming opioids. Several studies have discovered that young kids who have been exposed to opioids develop greater damages in overall intellectual capabilities and neurobehavioral functions than non-exposed children.